UJI UV-VIS LAPISAN TiO2/N2 UNTUK MENENTUKAN BAND GAP ENERGY - devi indriani; helga dwi fahyuan; ngatijo ngatijo (JOURNAL ONLINE OF PHYSICS, 2018)
[Title: TEST UV-VIS LAYER TiO2/N2 FOR DETERMINING BAND GAP ENERGY] The effect of nitrogen doping variation on energy band gap in TiO2 layer grown by doctor blade technique. The TiO2/N2 layer was prepared with concentrations of 0%, 15%, 25% and 25% calcined at 500°C for 3 hours. Characterization of band gap energy by using the UV-Vis spectrometer at a wavelength range of 200 nm-700 nm. The band gap energy is obtained by using the Swanepoel equation and Touch Plot method. The results showed that doping of nitrogen can decrease the band gap energy of 3.9250 eV, 3.8750 eV, 3.8375 eV and 3.9125 eV, respectively. The smallest energy band gap is obtained at 25% concentration that is 3.8375eV. Keywords: Coating TiO2/N2, transmittance, Band gap energy